Systematic synthesis of qualitative research - Saini, Michael; Shlonsky, Aron. (New York ; Oxford : Oxford University Press, 2012)
Social work researchers, educators, and doctoral students who are interested in systematic reviews will find the step-by-step format of this book invaluable for conducting their reviews both in the form of rapid evidence assessments and in high-quality critical reviews.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Social service -- Research -- Methodology; Qualitative research -- Methodology